2022
DOI: 10.1002/adfm.202207172
|View full text |Cite
|
Sign up to set email alerts
|

High Current‐Density‐Charging Lithium Metal Batteries Enabled by Double‐Layer Protected Lithium Metal Anode

Abstract: The practical application of lithium (Li) metal anode (LMA) is still hindered by non-uniformity of solid electrolyte interphase (SEI), formation of "dead" Li, and continuous consumption of electrolyte although LMA has an ultrahigh theoretical specific capacity and a very low electrochemical redox potential. Herein, a facile protection strategy is reported for LMA using a double layer (DL) coating that consists of a polyethylene oxide (PEO)-based bottom layer that is highly stable with LMA and promotes uniform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The symmetric cell using the prepared x PCMS‐ g ‐PEGMA/LN@Li demonstrated a very high dendrite suppression capability and volume change stability, as it operated stably for over 9100 h at a very high current density of 10 mA cm −2 . In other case, Kim et al 71 proposed a double‐layered protection layer consisting of a polyethylene oxide (PEO) layer and a cross‐linked polymer‐based layer on the Li metal surface. The bottom PEO layer has good binding characteristics with Li and high stability as it does not easily detach from Li during electrochemical reactions, and can suppress dendrite growth by creating uniform Li‐ion flux.…”
Section: Engineering Strategies To Design Practical Metal Anodementioning
confidence: 99%
“…The symmetric cell using the prepared x PCMS‐ g ‐PEGMA/LN@Li demonstrated a very high dendrite suppression capability and volume change stability, as it operated stably for over 9100 h at a very high current density of 10 mA cm −2 . In other case, Kim et al 71 proposed a double‐layered protection layer consisting of a polyethylene oxide (PEO) layer and a cross‐linked polymer‐based layer on the Li metal surface. The bottom PEO layer has good binding characteristics with Li and high stability as it does not easily detach from Li during electrochemical reactions, and can suppress dendrite growth by creating uniform Li‐ion flux.…”
Section: Engineering Strategies To Design Practical Metal Anodementioning
confidence: 99%
“…Xu et al [116] fabricated a soft-rigid HASEI layer consisting of PVDF, hexafluoropropylene (HFP), and LiF. Kim et al [117] reported a double HASEI layer. The PEO and LiTFSI on the bottom layer and the polymer composed of phosphoric acid 2hydroxyethyl methacrylate ester on the top layer could dramatically protect the Li metal anode against the electrolytes.…”
Section: Hybrid Artificial Sei (Hasei)mentioning
confidence: 99%
“…Uniform, ion-conductive, and chemically and mechanically stable protective layer coatings have been proven to effectively alleviate uncontrollable lithium dendrite growth and adapt to infinite volume changes in lithium metal. Liu et al developed a coating process to fabricate nanoscale arrayed pores, and by confinement at the nanoscale, the Li + flux of the anode can be distributed, thereby suppressing Li dendrites to a certain extent and achieving uniform Li nucleation and growth. Compared with those bare electrodes, Li metal batteries with electrodes coated with nanochannels have better CE and longer cycle life, which exhibit superior stability.…”
Section: Protection Of Interface Layermentioning
confidence: 99%